Pemanfaatan Media Video Dalam Mengatasi Kecemasan Primigravida Menghadapi Persalinan - Kristanti, Shinta; Suwoyo, Suwoyo; Pratiwi, Ika Yuni (Malang Journal of Midwifery (MAJORY), 2019)
For a mother's first pregnancy (primigravida) is one period of crisis in his life. In the third trimester is often called the waiting period with full alertness. Anxiety and fear of childbirth increases. Anxiety has no negative effects for pregnant women (especially pregnant first), with the anxiety will increase catecholamine levels so as to interfere with the progress of labor and prolonged labor occurs. Anxiety occurs in women with low knowledge about the process of childbirth. This is due to the lack of information obtained. This study aims to determine the effect of health education in primigravida third trimester of labor with video media to anxiety facing labor. The study design was praeksperimen with one group pretest posttest design. The study population number of 15 pregnant women, with simple random sampling obtained a sample of 14 respondents. The research instrument used was a questionnaire DASS, analyzed Wilcoxon Match Pairs Test using a standard error 0.05 then the Z table (1645) < Z count (3295). The results showed no effect of health education to primigravida third trimester of labor with video media to anxiety faced confinement in Puskesmas Blabak. Based on the results of the study, expected to be more varied health workers in giving information to primigravida before delivery. Keywords: Anxiety, Media Video, Health Education, primigravidas